Regulatory Variation in Functionally Polymorphic Globin Genes of the Bank Vole: A Possible Role for Adaptation - Dvořáková, Věra; Horníková, Michaela; Němcová, Lucie; Marková, Silvia; Kotlík, Petr (Frontiers in Ecology and Evolution, 2020)
Interaction between gene expression and protein-coding genetic variation is increasingly being appreciated as an important source of adaptive phenotypic variation. In this study, we used reverse transcription–qPCR to test for gene expression variation in two β-globin paralogs (HBB-T1 and HBB-T2) of the Eurasian bank vole (Myodes glareolus), which both display the same structural polymorphism Ser52Cys responsible for variation in Cys-based antioxidant capacity of red blood cells (RBCs). We first demonstrated that HBB-T1 is the major expressed adult HBB gene in the bank vole accounting for approximately 85% of total hemoglobin. We then measured the relative expression of the two homozygous genotypes in each gene and found that when present in HBB-T1, the oxidative-stress resistant Cys52 allele is significantly associated with higher expression ratio HBB T1:HBB-T2. The results further indicated that the Cys52 allele present in HBB-T1 was associated with higher normalized expression of that gene compared to the Ser52 allele, although this difference was statistically significant only when using one reference gene but not the other. We argue that, altogether, our results indicate the presence of a cis-acting regulatory genetic variation modulating the expression of the two alleles in HBB-T1. Previous studies indicated that the resistant RBC phenotype is likely beneficial under conditions conducive to oxidative stress. The duplicate HBB genes of the bank vole thus may represent a novel example of gene-regulatory genetic variation interacting with a well-defined protein-coding variation to control an adaptive trait.